2008
DOI: 10.1002/jbm.b.31234
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the behavior of different polypropylene meshes (heavy and lightweight) in an experimental model of ventral hernia repair

Abstract: New generation prosthetic biomaterials for abdominal wall repair have been designed to be less dense, by having larger pores than that of the standard polypropylene meshes, to improve abdominal wall compliance. The aim of the present study was to analyze the functional and morphologic properties of these new meshes. For this purpose, 7 x 5 cm(2) defects were created in the anterior abdominal wall of 36 male New Zealand White rabbits and repaired using different polypropylene meshes: a heavyweight mesh (HW), Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 16 publications
0
29
0
3
Order By: Relevance
“…That is PROLENE group exhibited more duration in LOH, analgesic use and in return to normal activities. [12,13] Lakshmi et al…”
Section: Discussionmentioning
confidence: 99%
“…That is PROLENE group exhibited more duration in LOH, analgesic use and in return to normal activities. [12,13] Lakshmi et al…”
Section: Discussionmentioning
confidence: 99%
“…Durante el proceso de cicatrización la malla va encogiéndose y disminuye su tamaño original al incorporarse a la pared del huésped, en ocasiones incluso más del 30-40 % de su tamaño original. Este fenómeno de retracción es muy elevado en las mallas de PTFE, y menor en las mallas compuestas de polipropileno de baja densidad [6][7][8][9][10][11][12][13][14][15] . 3.…”
Section: A Técnica Keyholeunclassified
“…Recent studies have confirmed reduced adhesion formation of less density for light-weight polypropylene meshes [5,6] as well as other favorable properties of these implants (i.e., reduced abdominal wall movement restriction and preservation of physiologic elasticity while sufficient strength for hernia repair is retained, reduced shrinkage of the implant, better biocompatibility with reduced foreign body reaction, and a smaller amount of material remaining in the recipient) [7][8][9][10]. But the risk still remains too high for uncovered intraperitoneal polypropylene application.…”
mentioning
confidence: 90%